2020
DOI: 10.1111/liv.14586
|View full text |Cite
|
Sign up to set email alerts
|

Combination of phosphodiesterase‐5‐inhibitors and beta blockers improves experimental portal hypertension and erectile dysfunction

Abstract: Background & Aims Phosphodiesterase‐5 inhibitors (PDE‐5‐I) are used for treatment of erectile dysfunction (ED), which is common in patients with cirrhosis. They may improve portal hypertension (PH), but contradictory data on efficacy and side‐effects have been reported. Non‐selective beta blockers (NSBB) reduce portal pressure, but might aggravate ED. Thus, we evaluated the combination of PDE‐5‐I with NSBB and its impact on PH and ED in experimental cirrhosis. Methods ED was assessed in cirrhotic patients (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…iNOS could not be found in healthy liver, but a marked expression was observed in early and progressed stages of TAA-induced liver damage. A subsequent study of Uschner et al using the BDL-model and the CCl 4 -model of liver cirrhosis confirmed the overexpression of eNOS and iNOS [ 97 ]. The latter data confirm the hypothesis of an iNOS upregulation in response to toxic stimuli.…”
Section: Pathophysiology Of Portal Hypertensionmentioning
confidence: 93%
See 4 more Smart Citations
“…iNOS could not be found in healthy liver, but a marked expression was observed in early and progressed stages of TAA-induced liver damage. A subsequent study of Uschner et al using the BDL-model and the CCl 4 -model of liver cirrhosis confirmed the overexpression of eNOS and iNOS [ 97 ]. The latter data confirm the hypothesis of an iNOS upregulation in response to toxic stimuli.…”
Section: Pathophysiology Of Portal Hypertensionmentioning
confidence: 93%
“…Therefore, this paper yielded the molecular basis for the action of PDE-5 inhibitors on PVP in liver cirrhosis. Again, the study of Uschner et al confirmed the overexpression of sGC and PDE-5 in the BDL-model and the CCl 4 -model of liver cirrhosis [ 97 ].…”
Section: Pathophysiology Of Portal Hypertensionmentioning
confidence: 93%
See 3 more Smart Citations